High Glucose in Diabetic Hyperglycemia Perturbs Lymphocyte SERCA-Regulated Ca2+ Stores with Accompanying ER Stress and Signaling Dysfunction - Md Nasim Uddin; James L. Graham; Peter J. Havel; Roshanak Rahimian; David W. Thomas (Biomolecules)
It is well recognized that patients with type 2 diabetes mellitus (T2DM) exhibit significant impairment of immune function resulting in a higher frequency of infections. We hypothesize in this study that a likely contributor to immune dysfunction in T2DM is alteration of T lymphocyte signaling functions induced by chronic hyperglycemia. In this study we have utilized the established UC Davis Type 2 Diabetes Mellitus (UCD-T2DM) rat model of human T2DM to investigate whether progressive hyperglycemia diminishes T cell receptor (TCR)-releasable endoplasmic reticulum (ER) Ca2+ stores, an essential early antigen-stimulated signal driving T cell activation. Furthermore, results from this study demonstrate that chronic hyperglycemia markedly alters the expression profile of the sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) Ca2+ ion pumps, which are the major enzymatic ion transporters maintaining replenished TCR-sensitive Ca2+ pools. We conducted companion experiments using Jurkat T lymphocytes exposed to high glucose which allowed finer resolution of early disruptions to ER Ca2+ store integrity and greater clarity on SERCA isoform-specific roles in diabetes-induced Ca2+ signal dysregulation. In summary, these experiments suggest that hyperglycemia in T2DM drives an ER stress state manifesting in reduced expression of the SERCA pumps, erosion of ER Ca2+ stores and culminating in T cell and immune dysfunction.